Suppression and promotion of tumor growth by monoclonal antibodies to ErbB-2 differentially correlate with cellular uptake. - Hurwitz, E (1995)
Amplification and overexpression of the erbB-2/neu protooncogene are frequently associated with aggressive clinical course of certain human adenocarcinomas, and therefore the encoded surface glycoprotein is considered a candidate target for immunotherapy. We previously generated a series of anti-ErbB-2 monoclonal antibodies (mAbs) that either accelerate or inhibit the tumorigenic growth of erbB-2-transformed murine fibroblasts. The present study extended this observation to a human tumor cell line grown as xenografts in athymic mice and addressed the biochemical differences between the two classes of mAbs. We show that the inhibitory effect is dominant in an antibody mixture, and it depends on antibody bivalency. By using radiolabeled mAbs we found that all of three tumor-inhibitory mAbs became rapidly inaccessible to acid treatment when incubated with tumor cells. However, a tumor-stimulatory mAb remained accessible to extracellular treatments, indicating that it did not undergo endocytosis. In addition, intracellular fragments of the inhibitory mAbs, but not of the stimulatory mAb, were observed. Electron microscopy of colloidal gold-antibody conjugates confirmed the absence of endocytosis of the stimulatory mAb but detected endocytic vesicles containing an inhibitory mAb. We conclude that acceleration of cell growth by ErbB-2 correlates with cell surface localization, whereas inhibition of tumor growth is associated with an intrinsic ability of anti-ErbB-2 mAbs to induce endocytosis. These conclusions are relevant to the selection of optimal mAbs for immunotherapy and may have implications for the mechanism of cellular transformation by an overexpressed erbB-2 gene.